Efficacy of intermittent prophylaxis vis a vis no prophylactic interventions in febrile seizure recurrence: randomised controlled trail - Bhoyar, Nitin; Bhaisara, Baraturam; Singh, Dinesh Kumar (International Journal of Research in Medical Sciences, 2019)
Background: To compare efficacy of intermittent prophylaxis during subsequent febrile episodes with antipyretics alone or antipyretics with anticonvulsant (clobazam) vis a vis no prophylactic interventions except need-based antipyretic measures in preventing recurrence of febrile seizures. Methods: This prospective randomized controlled interventional study was carried out in neurologically normal children. Study conducted over 14 months (March 2014 - May 2015), tertiary care hospital Mumbai. Inclusion criteria was, children aged from 6 month to 5 years with history of simple febrile seizure, lasting for less than 15 minutes, with Frequency less than one episode in 24 hours. Children with history of afebrile or complex febrile seizure, CNS comorbidity, family history of epilepsy, abnormal electroencephalogram, Unwillingness or non-feasibility of follow up were excluded from study. The patients were randomly grouped in A (No Prophylaxis n= 60), B (Antipyretic prophylaxis n=57) and C (Antipyretics + clobazam prophylaxis n=55). All cases were followed up telephonically every 15 days from date of first seizure as well as personal follow up at 1,3,6 months either in the hospital or at home. End point of study was taken as six months of follow-up from enrolment or lost-to-follow up. Efficacy of intervention was compared using chi-square test, Pearson chi-square test with/without Yates continuity correction and/or Fisher exact test, with p value of <0.05 as test of significance. Results: Sixty cases in group A developed febrile episodes and 6 of them developed recurrence of febrile seizures, with a recurrence rate of 10% among total cases and 9.67% among all febrile episodes. Recurrence rate was significantly higher (10%) in cases who did not receive any prophylactic intervention (Group A) as compared to pooled recurrence rate in group B and C together 1.78% (p=0.022). Conclusion: Regular antipyretic prophylaxis, alone or along with clobazam does not reduce the risk of recurrence in simple febrile seizures as compared to those who receive antipyretic intervention.